Surgeon adoption of immediate sequential bilateral cataract surgery in the United States from 2018 to 2022 - Ali, Muhammad; Dun, Chen; Chang, David F.; Son, Hyeck Soo; Woreta, Fasika A.; Soiberman, Uri S.; Prescott, Christina R.; Makary, Martin A.; Srikumaran, Divya (Journal of cataract and refractive surgery, 2025)
Purpose: - To assess 5-year trends in the rate of immediate sequential bilateral cataract surgery (ISBCS) and surgeon characteristics associated with performing ISBCS. - Setting:  - 100% Medicare Fee-For-Service beneficiaries from 2018 to 2022. - Design: - Cross-sectional study. - Methods: - ISBCS cases were identified among patients aged 65 years or older undergoing bilaterally performed cataract surgery (BPCS). Cochrane Armitage trend test was used to assess patient and surgeon characteristics over time. Multivariate logistic regression was used to evaluate surgeon characteristics associated with performing ISBCS. - Results: - Among 1 190 169 BPCS, 3954 (0.33%) were ISBCS. Quarterly ISBCS rate increased from 2.12 to 5.5 per 1000 BPCS (P < .001). Among 10 290 surgeons, 1119 (10.87%) performed ISBCS on some patients. Proportion of surgeons performing ISBCS per 1000 cataract surgeons increased from 15.63 during the first quarter of 2018 to 26.55 during the last quarter of 2022 (P < .001). Among the ISBCS surgeons, the proportion of ISBCS cases per 1000 BPCS doubled from 17.20 in 2018 to 35.50 in 2022 (P < .001). On multivariate analysis, surgeons in the highest surgical volume quartile (odds ratio [OR], 1.21; 95% CI, 1.01-1.45; Ref: lowest quartile), recent graduates (0 to 10 years: OR, 2.43; 95% CI, 1.87-3.15; Ref: ≥ 31 years), and surgeons in the West (OR, 2.408; 95% CI, 2.052-2.826; Ref: South) had higher odds of performing ISBCS. - Conclusions: - There was an increased rate of ISBCS possibly suggesting greater interest among patients and surgeons. Although the overall ISBCS rate remained low, the number of surgeons performing ISBCS increased. Higher volume surgeons, recent graduates, and those practicing in the West were more likely to perform ISBCS.